Optimization of Online Learning with A Combination of Offline Practices in The Post-Pandemic Era - Koeswanti, Henny Dewi (International Journal of Elementary Education, 2021)
The Covid-19 pandemic has had various impacts on all aspects of human life. One aspect that is affected is the education aspect. The Covid-19 pandemic has led to a transformation of learning methods. Learning that was originally carried out face-to-face has been transformed into distance learning, namely through online learning. The learning transformation certainly has obstacles that can hinder the implementation of the learning process. This study aims to describe educational problems that occur during the implementation of online learning. This research is a qualitative research using descriptive method. This study provides an overview of the implementation of online learning as well as solutions and efforts to optimize learning both online and offline. Data collection was carried out using the literature study method, namely reviewing references in the form of books and scientific articles related to the topic being studied. The data analysis technique used in this research is descriptive analysis technique. The results of this study indicate that during the Covid-19 pandemic, online learning can be carried out combined with offline activities for students. The implementation of these activities is of course by implementing strict health protocols and carried out in their respective homes.